‘Fit to work?’ An analysis of the supervision of employee attractiveness in the workplace - Travis, Daniela (2017)
This dissertation addresses the relationship between attractiveness and employability by looking at previous research on the links between attractiveness and increased career success. It goes on to look at how levels of attractiveness are maintained through organisational control using the specialised case study of Hooters. There are two broad research questions that I have chosen to address. Firstly, from a theoretical basis, I am going to research: how does your appearance affect your employability? Building on the answer to this question I am going to explore the question of: how are levels of attractiveness maintained and controlled within the workplace? A combination of interviews, media analysis, participant observation and an analysis of the Hooters training manual were used to ensure that data was collected through various avenues. The data collected from these methods was collated thematically through analysis and interpreted and compared accordingly. Results indicate that attractiveness plays an important role within employment. When looking at Hooters as a case study, attractiveness is maintained through group categorisation and affiliation, handbook instructions, jumpstart daily meetings and weight probation.